A land made from water: appropriation and the evolution of Colorado's landscape, ditches, and water institutions - Crifasi, Robert R., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2015)
Crifasi chronicles how the appropriation and development of water and riparian resources in Colorado has changed the face of the Front Range--an area that was once a desert and is now an irrigated oasis, suitable for the habitation and support of millions of people.--Provided by publisher.
Keywords: Water resources development -- Colorado -- History; Hydraulic engineering -- Colorado -- History; Water-supply -- Colorado -- History